Molecular Docking, Molecular Dynamics Simulation, and Pharmacophore-Based Virtual Screening Unveil Natural Compounds with TIM-3 Inhibitory Activity - Abdulrahim A. Alzain; Mohammed A. Almogaddam; Rayan Yousif; Mohammed Hamed Alqarni; Ahmed I. Foudah; Wadah Osman; Khaled M. Elamin; Hagar M. Mohamed; Ehssan Moglad; Ahmed Ashour; Reham M. Samra; Gamal A. Mohamed; et al. (Journal of Pharmacy and Bioallied Sciences, 2025)
Introduction: The aberrant expression of T cell immunoglobulin mucin-3 (TIM-3) has been linked to adaptive immunotherapy resistance and poor prognosis. Targeting TIM-3 has gained popularity due to positive outcomes in preclinical settings. Materials and method: This research explored the Supernatural 3.0 database for potential TIM-3 inhibitors. A pharmacophore-based virtual screening, molecular docking, and molecular dynamics simulations were conducted for 449,008 compounds. Compounds SN0085417 (-7.542 kcal/mol), SN0261906 (-7.036 kcal/mol), and SN0276180 (-6.871 kcal/mol) showed better docking scores. These compounds revealed remarkable hydrogen bonds and π–π stackings interactions with TIM-3 IgV domain. Results: The analysis of root-mean-square deviation (RMSD) and root-meansquare-fluctuation (RMSF) trajectories displayed stable interaction patterns with no substantial conformational changes in the TIM-3 backbone. Conclusion: These findings proposed SN0085417, SN0276180, and SN0261906 as TIM-3 inhibitors, which, with more extensive analysis, could undoubtably add to the realm of feasible TIM-3 based cancer immunotherapies.